Mathematical Reasoning Ability in Solving Flat Geometry Problems Based on Camper Type Adversity Quotient in Junior High School Students - Dewi, Nirmala; Talib, Ahmad; Djam’an, Nurwati (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This research employed a descriptive qualitative approach to analyse the mathematical reasoning abilities of junior high school students when solving plane geometry problems, specifically focussing on their camper type adversity quotient. The research subjects consist of two students who were selected based on the Adversity Response Profile (ARP) questionnaire scores, namely two camper subjects with moderate scores. Furthermore, the researcher gave mathematical reasoning test questions on the quadrilateral material and conducted interviews with each subject. The researcher checked the validity of the data by using source triangulation. The analysis of mathematical reasoning ability is based on three indicators: finding mathematical patterns to make generalisations, performing mathematical manipulations, and drawing conclusions while compiling evidence and providing reasons for the correctness of the solution. The results of this research showed camper-type students used inductive reasoning, which is good in determining mathematical patterns, but cannot make appropriate generalisations of the patterns that were found. In doing mathematical manipulation, there are camper-type students who use trial and error strategies in solving geometry plane problems. Camper-type students can draw conclusions from a geometry plane problem but have difficulties in gathering evidence and providing reasons for the correct problem-solving.